Analyzing the Sufficiency of Adaptation Options in Combating Climate Vulnerability in Bangladesh - , Md Rezaul Karim; , Marie Estelle Bumah Ateh (Archives of Current Research International, 2016)
Adaptation comprises one of the pertinent issues related to climate vulnerable countries like Bangladesh. Bangladesh is particularly vulnerable to the adverse effects of climate change with its manifestations being felt every year in the form of various natural disasters such as cyclones, floods, riverbank erosions, droughts, and salinity as a result of global warming. Predications indicate Bangladesh as the most vulnerable country in the world susceptible to climate change related disasters in the 21st century. This article therefore aims at providing an analysis on climate change vulnerability and fifteen (15) climate adaptation options adopted locally in the disaster prone areas of Bangladesh. The climate policy of Bangladesh is aimed at developing stable climate change strategies in order to achieve the sustainable development goal which forms a great of the vision 2021. The Government of Bangladesh together with some NGOs have committed to implementing different external climate change adaptation programmes. However, their climate adaptation strategies have been applied on a limited scale. Furthermore, the adaptive capacity of the indigenous practice is not strong enough to cope with shocks in the long run; especially natural disasters. Additionally, migration of affected people from disaster prone areas has been identified as an option not viable enough to sustain their livelihoods. Various initiatives (government including some NGO bodies) have been undertaken on the part of with the objective of motivating farmers to adopt new technological change. Some of them include: the introduction of flood and drought tolerance crop varieties. However, the extent to which farmers perceived these tolerant crop varieties was limited resulting in their poor adoption; as a result of poor knowledge, lack of input support and low information access. This report further suggests the need to determine the effectiveness of different adaption practices that were undertaken to combat climate change. In addition, a suggested framework consisting of the models of vulnerability, adaptation techniques and strategies to effectively diffuse climate change sensitive knowledge, skill and practices would be relevant for different stakeholders involved in the climate change debate to implement further climate change policies in Bangladesh.